Analisis Strategi Model Bisnis Produk Industri Kreatif Dengan Pendekatan Model Canvas (Studi Pada Industri Batik Laweyan Kota Surakarta) - Hariani, Danarti; Sutrisno, Sutrisno (Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
Currently, the world is entering the industrial era 4.0, namely the creative economy industry which develops creative ideas. Changes in consumers, technological developments and a competitive climate require the industry to renew its strategy by making innovations and constructive efforts so that the creative industry must improve itself to be able to compete in local and global markets. The Batik industry is one of the industries that is interesting to be studied, this is because batik is one of the world cultural heritages from Indonesia which must be protected and preserved. Surakarta is one of the cities which is famous for its Batik characteristics. As a design-based cultural city, batik is one of the leading products. Batik Solo has been proposed as a design-based creative city to the United Nations (UNESCO). The object of the research taken is the batik industrial area in Kampung Batik Laweyan, because Laweyan is the origin of batik created in Surakarta. Competition in the national and world batik industry will affect business development, so it requires a special strategy in facing competition, as well as using a model to structure its business. The purpose of this study is to determine the strategic model of the Laweyan batik industry with a canvas model by describing the facts of the economic potential of the Laweyan Batik industry and alternative business strategies with a canvas model approach in facing competition and maintaining the existence of Kampung Batik Laweyan as a sustainable batik industry icon in Surakarta.Keywords: Batik Laweyan Surakarta, Model Canvas, Creative Industry